What should be the Rotation Age and Harvest Management in Teak - Jha, Kaushalendra Kumar (Indian Forester, 2016)
This article is the outcome of author's view on the subject based on his field experience as a professional forester, his research work on the ecology of teak and reviewed literature on the subject. Although short rotation harvesting has its own value, long rotation is beneficial keeping in view GHG mitigation, paragon timber reputation and high value marketing of teak (Tectona grandis). Biological supplementing of the soil would be a useful management intervention to compensate nutrient drain from the soil due to timber harvest. However, delayed harvesting or longer rotation is recommended for two-pronged benefit- lower loss of nutrients and longer locking of Carbon.